A nano-Ti2AlC induced intracrystalline twinning strengthened TiAl alloy and preparation method thereof
By introducing nano-Ti2AlC into TiAl alloy and hot rolling treatment, the twinned structure is induced to form in its crystal, which solves the shortcomings of TiAl alloy in room temperature plastic toughness and high temperature strength, and significantly improves its mechanical properties.
Patent Information
- Application Number
- CN202310550468.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-05-16
AI Technical Summary
The existing TiAl alloys have shortcomings in room temperature plastic toughness and high temperature strength, and fail to effectively regulate the microstructure structure of its crystal, resulting in the problems of intrinsic brittleness and insufficient high temperature strength.
By introducing nano-Ti2AlC into TiAl alloy, using discharge plasma sintering technology and multi-pass hot rolling treatment, twinned crystal structures are induced to form in TiAl crystals, thereby improving its microstructure structure.
The room temperature and high temperature mechanical properties of TiAl alloy are improved, the density and mechanical properties are enhanced, and the problems of intrinsic brittleness and insufficient high temperature strength are solved.
Smart Images

Figure CN116590563B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of TiAl-based alloys, in particular to a nano-Ti2AlC-induced intracrystalline twinning-strengthening TiAl alloy and a preparation method thereof. Background Art
[0002] TiAl alloy has become a new type of lightweight high-temperature structural material with great application potential that can partially replace Ni-based high-temperature alloys due to its advantages such as low density, high specific strength and specific stiffness, and excellent high-temperature performance (good high-temperature strength and oxidation resistance). In recent years, with the rapid development of my country's aerospace and automotive fields, the thrust-to-weight ratio requirements for key core components such as aircraft and engines have become increasingly higher, and higher requirements have been put forward for the room temperature plasticity and toughness, high-temperature mechanical properties, etc. of TiAl alloys. In past studies, domestic and foreign researchers usually added alloying elements for alloying treatment to improve room temperature plasticity, high-temperature strength and high-temperature creep resistance. With the continuous development of composite technology, it has become a hot topic to improve and enhance the comprehensive mechanical properties of TiAl alloys by introducing reinforcements into TiAl alloys to play a synergistic role. Ti2AlC, as a layered ternary carbide, has excellent metal and ceramic properties. Similar density and thermal expansion coefficient effectively avoid the generation of large internal stresses between the two during the composite process. Therefore, the introduction of Ti2AlC can effectively improve the comprehensive mechanical properties of TiAl alloys on the basis of ensuring the excellent properties of TiAl itself.
[0003] For TiAl alloys with fine lamellar microstructures and excellent comprehensive mechanical properties, past studies have only focused on introducing reinforcing phases at TiAl grain boundaries, lamellar TiAl / Ti3Al phase boundaries, etc. to improve the room temperature and high temperature mechanical properties of TiAl alloys, without regulating the microstructure within the TiAl alloy crystal, so as not to fundamentally solve the problem of intrinsic brittleness and insufficient high temperature strength within the TiAl crystal. Summary of the invention
[0004] In order to solve the deficiencies in the prior art, the present invention provides a nano-Ti2AlC induced intracrystalline twinning toughening TiAl alloy and a preparation method thereof. A nano-Ti2AlC / TiAl composite material is prepared by spark plasma sintering technology, and is subjected to multi-pass rolling treatment, and nano-Ti2AlC is used to perform twinning sequence in the TiAl crystal. The purpose is to regulate the microstructure in the TiAl crystal, and to improve the room temperature and high temperature mechanical properties of the composite material by inducing twinning in the TiAl crystal with nano-Ti2AlC.
[0005] In order to achieve the above object, the specific scheme adopted by the present invention is:
[0006] A nano-Ti2AlC-induced intracrystalline twinning strengthening and toughening TiAl alloy is firstly prepared by SPS sintering to prepare a Ti2AlC / TiAl composite material, wherein the Ti2AlC / TiAl composite material is a full lamellar structure composed of lamellar γ-TiAl / α2-Ti3Al, and nano-Ti2AlC is precipitated in the TiAl crystal; then the alloy is subjected to multiple rolling processes to use nano-Ti2AlC to perform twinning sequence in the TiAl crystal.
[0007] As a preferred solution, the size of the matrix γ-TiAl / α2-Ti3Al layer is 150-250 μm, and the size of the nano-Ti2AlC precipitated in the TiAl crystal is 10-30 nm.
[0008] A method for preparing a nano-Ti2AlC-induced intracrystalline twinning-strengthening TiAl alloy, mainly comprising the steps of preparing a monolayer dispersed graphene, uniformly milling TiAl pre-alloyed spherical powder and the monolayer dispersed graphene by low-energy ball milling to obtain a composite powder, performing SPS sintering on the composite powder to obtain a composite material, and hot rolling the composite material;
[0009] The composite powder was placed in a furnace and heated to 1320°C at a rate of 100°C / min for SPS sintering. The holding time was 10 minutes and the sintering pressure was 45MPa. The composite powder was then cooled in the furnace to obtain a Ti2AlC / TiAl composite material with a full lamellar structure. At the same time, nano-Ti2AlC was in-situ precipitated in the TiAl crystal.
[0010] The Ti2AlC / TiAl composite material was subjected to multiple hot rolling passes, with a rolling temperature of 1200°C, a rolling speed of 0.5 m / s, a total rolling deformation of 10%, and a remelting period of 10 min between each pass.
[0011] As a preferred embodiment, the method for preparing a monolayer dispersed graphene is as follows: placing graphene nanosheets in deionized water and performing ultrasonic dispersion treatment to obtain a monolayer dispersed graphene nanosheet solution; placing the graphene nanosheet solution in a vacuum drying oven and performing vacuum drying treatment, and when the deionized water is completely evaporated, a monolayer dispersed graphene is obtained.
[0012] As a preferred solution, the graphene nanosheet has a thickness of 3-10 nm and a sheet diameter of 10 μm.
[0013] As a preferred solution, vacuum drying is performed in a vacuum drying oven at a temperature of 50-80° C. for 8-10 hours to obtain a single-layer dispersed graphene.
[0014] As a preferred solution, the atomic ratio of the TiAl pre-alloyed spherical powder is: Ti-48Al-2Cr-2Nb, the purity is 99.99%, and the spherical diameter is 150-250 μm.
[0015] As a preferred embodiment, the nominal composition of the composite powder is Ti-48Al-2Cr-2Nb-1.0C at%.
[0016] Beneficial effects:
[0017] Based on the nano-Ti2AlC prepared by the present invention, the intracrystalline twinning-toughening TiAl alloy is strengthened and toughened, starting from the two major disadvantages of TiAl alloy: intrinsic brittleness and insufficient high-temperature strength, the density of TiAl alloy is improved by multi-pass hot rolling technology, and the microstructure within the crystal is regulated. Driven by thermodynamics and kinetics, the nano-Ti2AlC with a hexagonal crystal structure can induce a large number of nano-twins to form in the TiAl crystal along the (0001) plane, which can effectively improve the room temperature and high temperature mechanical properties of the Ti2AlC / TiAl composite material. Therefore, the present invention is based on the material design principle of the functional element sequence structure, and uses the intracrystalline nano-Ti2AlC to design and control the microstructure of the TiAl alloy. By inducing intracrystalline twinning and toughening the TiAl alloy with nano-Ti2AlC, a new path and design direction can be opened up for the improvement of its mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a process flow chart of the present invention;
[0019] Figure 2 It is a schematic diagram of the preparation process of the present invention;
[0020] Figure 3 is a transmission image of the alloy prepared in Example 1;
[0021] Figure 4 This is a comparison chart of the high temperature compression strength of the alloy prepared in Example 1 before and after hot rolling. DETAILED DESCRIPTION
[0022] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] A nano-Ti2AlC induced intragranular twinning strengthened TiAl alloy, the composite material is a full lamellar structure composed of lamellar γ-TiAl / α2-Ti3Al, and contains nano-Ti2AlC precipitation in the TiAl crystal. Subsequently, multiple tests were carried out on a Φ180mm×400mm two-roll hot rolling test machine with different rolling deformation amounts. While improving the material density, the nano-Ti2AlC in the TiAl crystal induced twinning to further improve the mechanical properties of the composite material.
[0024] A method for preparing a nano-Ti2AlC-induced intragranular twinning-strengthening TiAl alloy mainly comprises the following steps:
[0025] Step 1, ultrasonic dispersion: placing graphene nanosheets with a thickness of 3 to 10 nm and a sheet size of 10 μm in deionized water, and performing ultrasonic dispersion treatment for 30 to 50 minutes to obtain a monolayer dispersed graphene nanosheet solution; vacuum drying the solution in a vacuum drying oven at a temperature of 50 to 80° C. for 8 to 10 hours, and wait for the deionized water to completely evaporate to obtain a monolayer dispersed graphene;
[0026] Step 2, low-energy ball milling: put TiAl pre-alloyed spherical powder (Ti-48Al-2Cr-2Nb) with a purity of 99.99% and a ball diameter of 150-250 μm and the graphene nanosheets dried in step 1 into a ball mill filled with argon (atomic ratio: Ti-48Al-2Cr-2Nb-1.0C), and use low-energy ball milling to evenly disperse the graphene nanosheets around the spherical TiAl pre-alloyed spherical powder, so as to make the graphene nanosheets diffuse more evenly in the form of carbon atoms during the sintering temperature rise process; during ball milling, 5mm-10mm zirconia balls are used as ball milling media, the ball-to-material ratio is 10:1, the ball milling speed is 100r / min, and the ball milling time is 10-15h; anhydrous ethanol is added as a process control agent during low-energy ball milling to avoid mechanical alloying during low-energy ball milling;
[0027] Step 3, SPS sintering: The composite powder prepared in step 2 is subjected to spark plasma sintering (SPS) to prepare a Ti2AlC / TiAl composite material with a full lamellar structure, and nano-Ti2AlC is precipitated in situ in the TiAl crystal; in detail, the SPS sintering is heated to 1320°C at a rate of 100°C / min, the holding time is 10min, and the sintering pressure is 45MPa; under high temperature conditions, the graphene nanosheets are fully diffused and dissolved in the TiAl matrix in the form of carbon atoms, and when cooling with the furnace, the carbon atoms are driven by thermodynamics and kinetics, and are transformed from disordered solid solutions to ordered nano-Ti2AlC (10~30nm) existing in the TiAl crystal;
[0028] Step 4, hot rolling treatment: the Ti2AlC / TiAl composite material prepared above is cut into a thin plate with a length of 180 mm, a width of 90 mm and a thickness of 10 mm, and a multi-pass rolling test is carried out on a two-roll hot rolling test machine. The rolling temperature is 1200°C, the rolling speed is 0.5 m / s, the rolling passes are set to 6 passes, the total rolling deformation is 10%, and the furnace is returned to the furnace for 10 minutes between each pass; Ti2AlC is a typical hexagonal crystal structure. During the unidirectional hot rolling process, the nano-Ti2AlC in the TiAl crystal can slide along the (0001) crystal plane and induce the TiAl matrix with less slip system to produce nano-deformation twins, and produce numerous twin boundaries to effectively refine the TiAl matrix, which can improve the comprehensive mechanical properties of the composite material.
[0029] Example 1
[0030] A method for preparing a nano-Ti2AlC-induced intragranular twinning-strengthening TiAl alloy, the process flow chart and the schematic diagram of the preparation process are shown in FIG. Figure 1 and Figure 2 As shown, the specific steps are as follows:
[0031] Step 1, ultrasonic dispersion: placing graphene nanosheets (thickness 3-10 nm, sheet size 10 μm) in deionized water and performing ultrasonic dispersion treatment for 50 min to obtain a solution of monolayer dispersed graphene nanosheets; placing the solution in a vacuum drying oven at 80° C. for 8 h, and waiting for the deionized water to completely evaporate to obtain a monolayer dispersed graphene;
[0032] Step 2, low-energy ball milling: TiAl pre-alloyed spherical powder (Ti-48Al-2Cr-2Nb) and the graphene nanosheets dried in step 1 are placed in a ball mill filled with argon (atomic ratio: Ti-48Al-2Cr-2Nb-1.0C); low-energy ball milling is used to evenly disperse the graphene nanosheets around the spherical TiAl pre-alloyed spherical powder, so that the graphene nanosheets can be diffused more evenly in the form of carbon atoms during the sintering temperature rise process; the selected Ti-48Al-2Cr-2Nb spherical pre-alloyed powder has a purity of 99.99% and a ball diameter of 150-250μm; zirconium oxide balls are used as ball milling media (5mm-10mm), the ball-to-material ratio is 10:1, the ball milling speed is 100r / min, and the ball milling time is 10h; and anhydrous ethanol is added as a process control agent to avoid mechanical alloying during low-energy ball milling;
[0033] Step 3, SPS sintering: The composite powder prepared in step 2 is subjected to a spark plasma sintering (SPS) experiment, the temperature is raised to 1320°C at a rate of 100°C / min, the holding time is 10min, and the sintering pressure is 45MPa, so that the graphene nanosheets are fully and evenly diffused into the TiAl matrix in the form of carbon atoms under high temperature conditions; a Ti2AlC / TiAl composite material with a full lamellar structure is prepared, and nano-Ti2AlC (10~30nm) is precipitated in the TiAl crystal by aging;
[0034] Step 4, hot rolling treatment: The Ti2AlC / TiAl composite material prepared above is subjected to a multi-pass rolling test on a two-roll hot rolling test machine. A thin plate with a length of 180 mm, a width of 90 mm, and a thickness of 10 mm is cut from the cylindrical sample as a rolled plate. The rolling temperature is 1200°C, the rolling speed is 0.5 m / s, the rolling passes are set to 6 passes, and the total rolling deformation is about 10%. At the same time, each pass is returned to the furnace for 10 minutes.
[0035] Ti2AlC is a typical hexagonal crystal structure. During the unidirectional hot rolling process, the nano-Ti2AlC precipitated in the TiAl crystal can slide along the (0001) crystal plane and induce the TiAl matrix with less slip system to produce nano-deformation twins, forming numerous twin boundaries to effectively refine the TiAl matrix. Please refer to Figure 3 Then the composite material prepared in this embodiment was tested for high temperature compressive strength before and after hot rolling. The results are as follows: Figure 4 As shown, it shows that hot rolling treatment can effectively improve the room temperature and high temperature mechanical properties of the alloy.
[0036] Comparative Example 1
[0037] The implementation methods of steps 1 to 3 in this embodiment are the same as those in embodiment 1, except that the rolling deformation amount adopted in this embodiment during the multi-pass hot rolling test is about 5%. Since the multi-pass rolling deformation amount is small, sufficient dynamic conditions cannot be provided for the nano-scale Ti2AlC induced twins in the TiAl crystal.
[0038] Comparative Example 2
[0039] The implementation methods of steps 1 to 3 in this embodiment are the same as those in embodiment 1, except that the rolling deformation amount adopted in this embodiment during the multi-pass hot rolling test is 15%. Under this rolling deformation condition, although nano-Ti2AlC in TiAl crystals can induce the formation of nano-deformation twins, the large rolling deformation amount leads to the formation of defects such as micropores and microcracks, thereby sharply reducing the performance.
[0040] In summary, in the Ti2AlC / TiAl composite material, when the rolling deformation is 10%, the nano-Ti2AlC in the TiAl crystal can effectively induce TiAl to form a large number of nano-deformation twins and improve the high-temperature mechanical properties of the composite material.
[0041] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a TiAl alloy strengthened by nano-Ti2AlC-induced intragranular twinning, characterized in that: The method mainly includes the steps of preparing a monolayer dispersed graphene, uniformly milling TiAl pre-alloyed spherical powder and the monolayer dispersed graphene by low-energy ball milling to obtain a composite powder, performing SPS sintering on the composite powder to obtain a composite material, and performing hot rolling treatment on the composite material; The SPS sintering step is as follows: placing the composite powder in a furnace, heating the temperature to 1320°C at a rate of 100°C / min for SPS sintering, holding the temperature for 10 minutes, and sintering at a pressure of 45MPa, and then cooling the furnace to obtain a Ti2AlC / TiAl composite material having a full lamellar structure composed of lamellar γ-TiAl / α2-Ti3Al, and simultaneously precipitating nano-Ti2AlC in situ in the TiAl crystal; The hot rolling treatment steps are: performing multiple hot rolling on the Ti2AlC / TiAl composite material, with a rolling temperature of 1200°C, a rolling speed of 0.5m / s, a total rolling deformation of 10%, and a 10min remelting period between each pass, and using nano-sized Ti2AlC to perform twinning sequence in TiAl crystals.
2. The method for preparing a nano-Ti2AlC-induced intragranular twinning-strengthening TiAl alloy according to claim 1, characterized in that: The size of the γ-TiAl / α2-Ti3Al is 150-250 μm, and the size of the nano-Ti2AlC precipitated in the TiAl crystal is 10-30 nm.
3. The method for preparing a nano-Ti2AlC-induced intragranular twinning-strengthening TiAl alloy according to claim 1, characterized in that: The method for preparing monolayer dispersed graphene is as follows: placing graphene nanosheets in deionized water and performing ultrasonic dispersion treatment to obtain a monolayer dispersed graphene nanosheet solution; placing the graphene nanosheet solution in a vacuum drying oven and performing vacuum drying treatment, and when the deionized water is completely evaporated, a monolayer dispersed graphene is obtained.
4. The method for preparing a nano-Ti2AlC-induced intragranular twinning-strengthening TiAl alloy according to claim 3, characterized in that: The thickness of graphene nanosheets is 3~10nm and the diameter of the sheet is 10μm.
5. The method for preparing a nano-Ti2AlC-induced intragranular twinning-strengthening TiAl alloy according to claim 3, characterized in that: The monolayer dispersed graphene was obtained by vacuum drying in a vacuum drying oven at a temperature of 50-80°C for 8-10 hours.
6. The method for preparing a nano-Ti2AlC-induced intragranular twinning-strengthening TiAl alloy according to claim 1, characterized in that: The atomic percentage of the TiAl pre-alloyed spherical powder is: Ti-48Al-2Cr-2Nb, the purity is 99.99%, and the ball diameter is 150~250μm.
Citation Information
Patent Citations
Preparation method of in-situ self-generated micro-nano particle reinforced TiAl-based composite material
CN110172604A
TiAl-based composite material with two-stage reinforced three-dimensional network structure and preparation method of TiAl-based composite material
CN115921874A